DIGITAL PLATFORMS AND LINGUOPRAGMATIC APPROACH IN TEACHING LOGISTICS TERMINOLOGY: A METHODOLOGICAL PERSPECTIVE - Safarova Dilnavoz Ravshan qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the intersection of digital technology and linguopragmatic competence in teaching logistics English for Specific Purposes (ESP). As global supply chain communication increasingly relies on digital platforms, learners of logistics terminology require not only lexical knowledge but also the pragmatic capacity to deploy specialist language in authentic professional contexts. The study argues that digital tools — including corpus-based platforms, authentic online resources, and AI-assisted practice environments — serve as effective mediators for developing linguopragmatic awareness in first-year logistics students. A methodological framework is proposed in which digital resources are integrated into a linguopragmatic instructional sequence, enabling learners to encounter, analyse, and produce logistics terminology within contextually meaningful communicative situations.